Parerga to the Stadiasmus Patarensis (16): The Roads, Settlements and Territories - Fatih Onur (Gephyra, 2016)
In this contribution the author discusses three issues relating to the course of the roads and settlements mentioned in the Stadiasmus Patarensis (SP): 1- All the roads recorded on the SP were measured from within the borders of town centres, except for those settlements given with the preposition διά. 2- The territories of the settlements were observed in the composition of the road list and indicated through διά when required. 3- All the settlements recorded on the SP had an autonomy with reference to fiscal basis and possessed territorial rights. The author begins the discussion with the use of the prepositions διά, εἰς and ἐπί, which relate to territories or natural formations, town zones and borders respectively, and the articles that were not used for the settlement names, but for the regions or natural formations recorded on the SP. The author understands the SP was not constructed as a route guide for travellers, as it does not provide “routes” (itinera) but “roads” (viae) and, in consequence, it should be regarded as an official inventory of the roads, and consequently it is suggested that the recorded distances indicate the actual lengths of the roads between town-zones of settlements. Finally, based upon the argumentation outlined above, the author points out the autonomous nature of the settlements recorded in the SP. He also discusses the possible reasons for the omission of some ports, and concludes that it was because they were either, not poleis at the time or, they were ports under the control of other settlements, such as Andriake of Myra, with the roads given to the cities to which these ports belonged.